MANAGING PORTFOLIO OF CUSTOMER RELATIONSHIPS IN KNOWLEDGE-INTENSIVE SERVICES - M. Orlova; S. Silina (Вестник университета)
A study of application of project-oriented approach to managing customer relationships in knowledge-intensive projects. The determining role of managing “portfolio of customer relationships” in achieving competitive advantage in contemporary market environment for the sector of knowledge-intensive services is proved. The methods of marketing management of “portfolio of customer relationships” in project-oriented organizations are proposed.